Pengembangan Augmented Reality Menggunakan Metode AGILE Sebagai Media Pembelajaran Wisata Religi - Irfan Ali; Ade Irma Purnamasari; Ahmad Faqih; Muhammad Izaat Luthfi; Syamsul Lubis (JURIKOM (Jurnal Riset Komputer), 2022)
Knowledge of Cirebon cultural heritage that can be used as tourist attractions with religious nuances includes the Kesepuhan Palace, Sunyaragi Water Park, At-Taqwa Mosque and Belawa Cirebon, This tourist attraction introduces a cultural history that has an Islamic nuance because Cirebon is the first place for the teachings of Islam in the West Java area, but the management is not optimal, it requires information facilities using augmented reality technology to increase tourist interest in visiting, The purpose of this study is to apply augmented reality to introduce and provide information about cultural heritage in Cirebon, which is presented attractively in 3 dimensions and in real time that combines real content with virtual oriented real world that can be seen directly by the user, This study uses the agile method in the development of augmented reality-based systems because this method has no limits in iterating and making the system carried out in stages and focuses on producing quality products. The results of functional testing of the augmented reality application features of religious tourism can run well and users state that they are satisfied with the appearance and workings of this application so that it can help increase public interest in religious and historical tourism in the city of Cirebon